The Effect of Organizational, Individual, and Demographic Factors on the Whistle-blowing Intention - Yustrida Bernawati; Giovani Beatrice Napitupulu (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2018)
Internal auditors play an important role in their organization, to prevent, detect and correct violations. This study aimed to obtain information and empirical evidence of the influence of organizational, individual, and demographic factor to the whistleblowing intention (reporting violations). The respondents in this study were 52 internal auditors working in the Financial and Development Supervisory Board (BPKP) East Java Province. The method used in this research was a quantitative method using multiple linear regression analysis. The results showed that organizational, individual, and demographic factors simultaneously had a significant effect on whistleblowing intention. Meanwhile, partially, the test result indicated that the individual factors (organizational commitment and personal cost) and demographic factors (ethnicity and gender) had a significant effect on the whistleblowing intention, whereas the organizational factors (managerial status) and individual factors (locus of control) had no effect on the whistleblowing intention.